GIDS - A system for combining RFID-based site information and web-based data for virtually displaying the location on handheld devices - Löffler, Andreas; Gerhäuser, Heinz; Kuznetsova, Dina; Wissendheit, Uwe (2008 IEEE International Conference on RFID, 2008)
This paper describes an application that uses RFID information to display location-based coordinates on a map. An RFID transponder containing the coordinates of the transponder's position as well as optional information, e.g. about the location, building, neighborhood, is read out by a specially developed RFID reader. The reader processes the information and forwards it to a handheld device, which is wireless connected to a database/intranet or the Internet. In a first step this handheld device is a Tablet PC running a software application, which processes the data received from the transponder and maps the transponder's position on a graphical output. The graphical output is based on the Google Maps environment and implemented in a web browser plugin. For this purpose, the software application uses specific scripts (implemented in JavaScript), which generate standard and custom maps based on the Google Maps API. In a second step, the application has been ported to a mobile platform, consisting of a mobile phone, with a NFC capable RFID reader. © 2008 IEE
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.komele.gidsas